The Effect of Government Expenditures, Domestic Invesment, Foreign Invesment to the Economic Growth of Primary Sector in Central Kalimantan - Magdalena, Suryani; Suhatman, Rony (Budapest International Research and Critics University, 2020)
This research aims to the effect of government expenditures, domestic invesment, and foreign invesment to the economic growth of primary sector in central Kalimantan. This research is quantitative research with used analyzed of mutiple linier regression. Collection the variable data by library methods based on secondary data with times series on 1990-2019. Research results show that the Government Expenditures, Domestic Invesment, and Foreign Invesment for simultante has significant effect and positive to the Economic Growth of Primary Sector. For while partial that the Government Expenditures has significant effect and positive to the Economic Growth of Primary Sector meanwhile Domestic Invesment and Foreign Invesment has not significant effect.